Improved strontium hexaferrites: An overview of current progress in synthesis, properties, and applications - Gupta A.; Roy P.K. (My University, 2025)
Hard magnets (HMs) are significant components in various applications like rotating machines, telecommunication, computer devices, sensors, and many more. In the HM group, permanent magnets are extensively used due to their high energy product, though they are costly and contain rare earth (RE) elements. Advancements in the magnetic properties of non-RE-based hard magnets can fulfill the technology gap between non-RE and expensive RE-based hard magnets. Hexaferrite magnets represent the largest magnet group being used nowadays by volume, in which strontium hexaferrite (SrM) is a widely used non-RE hard magnet. It is the most faithful base magnet in terms of abundance and economic balance, which requires more or less reformation and advancement in the aspect of magnetic properties. SrMs are ferrimagnetic materials, and their magnetic properties are inherently linked to the microstructures. It can be upgraded to attain high (BH)max and high curie temperature by refining its magnetic properties. Improvement in its Ms and Hc, even mildly, could open up the possibilities of large-scale immersion of strontium hexaferrite-based magnets in the vast field of permanent magnet applications. In the past several years, enormous improvement has been made toward enhancing the physical and magnetic properties of SrM. Identifying the synthesis parameters as well as the microstructural changes is essential for designing and improvisation of magnets. The current progress in the magnetic properties of SrM (especially high Ms and high Hc) by synthesis parameters and different substituting elements is briefly covered in this review, along with the applications and future aspects of Sr-hexaferrite-based magnets. © 2024 Elsevier B.V.